Quantum decoherence of phonons in Bose–Einstein condensates - Howl, Richard; Sabín, Carlos; Hackermüller, Lucia; Fuentes, Ivette (Institute of Physics, 2017)
We apply modern techniques from quantum optics and quantum information science to Bose–Einstein condensates(BECs)in order to study, for the first time, the quantum decoherence of phonons of isolated BECs. In the last few years, major advances in the manipulation and control of phonons have highlighted their potential as carriers of quantum information in quantum technologies, particularly in quantum processing and quantum communication. Although most of these studies have focused on trapped ion and crystalline systems, another promising system that has remained relatively unexplored is BECs. The potential benefits in using this system have been emphasized recently with proposals of relativistic quantum devices that exploit quantum states of phonons in BECs to achieve, in principle, superior performance over standard non-relativistic devices. Quantum decoherence is often the limiting factor in the practical realization of quantum technologies, but here we show that quantum decoherence of phonons is not expected to heavily constrain the performance of these proposed relativistic quantum devices.